Phinestic learning / Zunaidah Ab Hassan … [et al.] - Ab Hassan, Zunaidah; Adam, Norashikin; Azmanudin, Nurzahirah Adhani; Sallehudin, Nur Sufia Malissa; Mohamad Isa, Zulaikha Qystina; Muhamad Saferi, Nur Amani Aimi; Abu Bakar, Aisyah Najwa; Mohd Razib, Faris Hamizan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The idea of our project is to develop a personal finance visual animation designed to be viewed on devices for slow learner’s students in managing their finances as well as providing an introduction to financial management. “Phinestic Learning” attempts to provide opportunities for slow learners to advance their financial planning. "Phinestic Learning” will give them access to learning materials that suit their needs, including basic concepts of spending and saving. Students with learning disabilities can have better understanding about the importance of managing their money by helping them become more independent and responsible in financial aspects throughout their life. The students with impairments can utilize and comprehend our application more easily. This application will provide short animated educational videos from various cartoon animation to explain financial concept in an interactive way. To make learning more fun, this application also provides interactive and educational games to train their financial skills through fun and interesting activities. Other features included is an artificial intelligence that uses money scanning to assist in calculating the amount of money pocket. With a combination of short animated educational videos, mini games and money scanner, this application will provide a complete and enjoyable learning experience for student with learning disabilities in the field of financial planning.